2017
DOI: 10.1007/s13238-017-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

Correction of β-thalassemia mutant by base editor in human embryos

Abstract: β-Thalassemia is a global health issue, caused by mutations in the HBB gene. Among these mutations, HBB −28 (A>G) mutations is one of the three most common mutations in China and Southeast Asia patients with β-thalassemia. Correcting this mutation in human embryos may prevent the disease being passed onto future generations and cure anemia. Here we report the first study using base editor (BE) system to correct disease mutant in human embryos. Firstly, we produced a 293T cell line with an exogenous HBB −28 (A>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
127
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(136 citation statements)
references
References 28 publications
2
127
1
3
Order By: Relevance
“…On a genome‐wide scale using high coverage whole genome resequencing data for five mutant animals (> 40 × ) and four controls, one additional off‐target mutation predicted at four different target sites in all the animals was revealed, which was confirmed to be somatic (Figs A,B). Along with previous studies in human embryos , mice , and our recently study in sheep , these results indicated a low incidence of BE3‐induced off‐target mutagenesis, and the off‐target mutations were dependent largely on sgRNA design.…”
Section: Discussionsupporting
confidence: 80%
“…On a genome‐wide scale using high coverage whole genome resequencing data for five mutant animals (> 40 × ) and four controls, one additional off‐target mutation predicted at four different target sites in all the animals was revealed, which was confirmed to be somatic (Figs A,B). Along with previous studies in human embryos , mice , and our recently study in sheep , these results indicated a low incidence of BE3‐induced off‐target mutagenesis, and the off‐target mutations were dependent largely on sgRNA design.…”
Section: Discussionsupporting
confidence: 80%
“…Together, these components enable efficient and permanent C•G to T•A base pair conversion in bacteria, yeast 4,9 , plants 10,11 , zebrafish 8,12 , mammalian cells 38,13,14 , mice 8,15,16 , and even human embryos 17,18 . Base editing capabilities have expanded through the development of base editors with different protospacer-adjacent motif (PAM) compatibilities 7 , narrowed editing windows 7 , enhanced DNA specificity 8 , and small-molecule dependence 19 .…”
mentioning
confidence: 99%
“…Summarizing, rice plants can be affected by complex genome x environment x management interactions which results in phenotypic plasticity as a result of the variability of genetic components. Whether by on side, recently advances have been made in genetic analysis, propitiated by development of new approaches as such CRISPR/Cas (Cong et al, 2013) and base editor (Liang et al, 2017), on the other hand, in respect to non-invasive physiological phenotyping, there are scarcity of large-scale analyses of the underlying physiological mechanisms that plants trigger in response to environmental stimulus. In this sense, even in an initial phase, our data indicate that external phenotype such as spikelet sterility and 1000-grain weight is determined by the sum of the complex interactions resultant of an internal, physiological, and biochemical phenotype.…”
Section: Discussionmentioning
confidence: 99%